A New Approach Towards Improving The “growth-oriented” Entrepreneurship Environment, With A Study Of Examples From Some Countries - Afif, Hana (جامعة الوادي - University of Eloued, 2023)
This study attempts at answering a problem centered on the clarification of the modern approach to growth entrepreneurship, and the question of improving its environment. The growth entrepreneurial ecosystem is discussed through examples of countries that have adopted this new approach. This study concludes that companies that follow the traditional policy, aim at generating and strengthening sources of finance and entrepreneurship that target emerging companies, in particular, in the form of investment capital and seek to finance it, by putting emphasis on the innovation factor,while companies that rely on an entrepreneurial approach are oriented to and emphasize growth work by focusing on high potentials and on entrepreneurs with the greatest economic potential. Among the examples presented, it was noted that, in order to improve the ecosystem of growth-oriented entrepreneurship at the level of the Caribbean island countries, the Program for Innovative Entrepreneurship adopted was established and has two levels: two sector programs targeting climate and mobility innovations, and three non-sector programs targeting growth-oriented entrepreneurship
مقال
Keywords: Entrepreneurship ; growth-oriented entrepreneurship ; ecosystem ; growth-oriented entrepreneurial ecosystem.